Size Dependence Unveiling the Adsorption Interaction of High-Density Lipoprotein Particles with PEGylated Gold Nanoparticles in Biomolecular Corona Formation - Jang, Gwi Ju (Langmuir : the ACS journal of surfaces and colloids, 2021)
Apolipoproteins have been often found to be highly enriched in the serum protein coronas produced on various engineered nanoparticles (NPs), which is also known to greatly influence the behaviors of protein corona NPs in the biological systems. As most of the apolipoproteins in blood are associated with lipoproteins, it suggests the active involvement of lipoproteins in the formation of biomolecular coronas on NPs. However, the interactions of lipoprotein complexes with NPs in the corona formation have been rarely understood. In this study, to obtain insights into the interactions, the formation of biomolecular coronas of high-density lipoproteins (HDLs) on the PEGylated gold NPs (PEG-AuNPs) of various sizes (20-150 nm dia.) was investigated as a model system. The results of this study revealed a noticeable size dependence, which is a drastic increase in the affinity of HDL for larger NPs and thus less-curved NP surfaces. For example, only a few HDLs per NP, which correspond to 5% surface coverage, were found to constitute the hard coronas of HDLs on 20 nm PEG-AuNPs, whereas 73% surface coverage was assessed for larger 150 nm PEG-AuNPs. However, the relative affinities of HDL and apolipoprotein A-1 (APOA1) examined in competition with human serum albumin exhibited the opposite size dependences, which suggests that the adsorption of HDLs is not driven by the constituent protein, APOA1. In fact, the total strength of non-covalent intermolecular interactions between a HDL particle and a NP relies on the physical contact between the two particles, which thus depends on the varying curvatures of spherical NPs in this case. Therefore, it was concluded that it is whole HDL complex that interacts with the spherical PEG-AuNPs in the initial stage of adsorption toward biomolecular coronas, which is unveiled by the distinct size dependence observed in this study